FBXO10 Drives Hepatocellular Carcinoma Proliferation via K63-Linked Ubiquitination and Stabilization of FRMPD1 - Wuguang Liu; Bin Xu; Kashif Kifayat; Yuhong Xie; Xiaolong Liu; Chengyong Dong; Liming Wang (Current Issues in Molecular Biology)
Aberrant ubiquitination drives hepatocellular carcinoma (HCC) progression, yet the role of FBXO10—a key F-box E3 ubiquitin ligase component—remains uncharacterized. Through bioinformatics analyses and functional validation, we establish FBXO10 as a critical oncogenic driver in HCC. Transcriptomic data from public databases (TIMER, UALCAN, GEO) revealed significant FBXO10 upregulation in HCC tissues, with elevated expression predicting advanced tumor stage, metastasis, and reduced survival. Functionally, FBXO10 silencing suppressed HCC cell proliferation while its overexpression promoted tumor growth. Mechanistic studies revealed that FBXO10 directly interacts with FRMPD1 to mediate its K63-linked polyubiquitination and stabilization, independent of transcriptional regulation. FRMPD1 restoration rescued FBXO10-mediated proliferation, confirming its role as the key downstream effector. Clinically, FBXO10 expression correlated with TP53 mutations and adverse clinicopathological features. Our findings reveal a novel FBXO10–FRMPD1 axis promoting hepatocarcinogenesis through post-translational stabilization, positioning FBXO10 as both a prognostic biomarker and therapeutic target in HCC.